Optimization of Temperature and Time for High-Quality Roasted Barley (Kolo) - Bimrew, Tewodros Mebratie; Yihune, Surafel; Nyambayo, Isabella (Universitas Ahmad Dahlan, 2025)
The consumption of roasted barley (kolo) is prevalent in all regions of Ethiopia. However, high-temperature heat treatment can result in the formation of acrylamide in roasted starchy foods. Acrylamide can be a health hazard if continuously consumed at high levels. This research contributes to optimize temperature and duration of roasting barley and investigate their impact on acrylamide formation, sensory profile, and nutritional profile of kolo sourced from both street vendors and industrial processors in Addis Ababa, Ethiopia. Locally produced kolo samples exhibited higher acrylamide contents ranging from 216.60 to 334.80μg/kg, while industrially processed kolo had lower values ranging from 200.28 to 308.95μg/kg. Results indicate that roasting temperature and duration significantly (p<0.05) affected acrylamide levels of kolo. The optimal roasting conditions of 352 ℃ for duration of 2 minutes gave desirability of 0.71. The optimum roasting conditions resulted in kolo with acrylamide of 148.64μg/kg, protein of 11.88%, ash of 3.28%, fat of 2.80%, crude fiber of 14.72%, carbohydrates of 67.35%, lightness (L*) of 57.50%, yellowness (b*) of 33.89%, redness (a*) of 15.52%, taste of 8.35, texture of 8.92, odor of 8.10 and overall sensory acceptability score of 8.18. Roasting barley grains transform them into value-added products and/ or nutritional food ingredients.